A Case Study in Bloggership - D. Gordon Smith (Washington University Law Review, 2006)
This paper makes the case that generally, bloggership should be treated as a form of service for administrative purposes. On the other hand, in close cases of tenure and promotion, a record of high-quality bloggership could weigh in a candidate’s favor on scholarship. This paper seeks to advance the process of legitimizing blogging as a useful scholarly endeavor—not as a substitute for long-form legal scholarship, but as a meaningful appendage.
Keywords: Law -- Study & teaching; Blogs; Walt Disney Co. Derivative Litigation; In re 906 A.2d 27 (Del. 2006); Duty of care (Law); Fiduciary duties; Good faith (Law); United States